Mechanisms of resistance to EGFR-targeted therapies in colorectal cancer: more than just genetics - Parseghian, Christine; Eluri, Madhulika; Kopetz, Scott; Raghav, Kanwal (Frontiers in Cell and Developmental Biology, 2023)
The development of acquired resistance to anti-EGFR therapies remains poorly understood, with most research to date exploring, and trying to overcome, various genomic mechanisms of resistance. However, recent work supports a model of resistance whereby transcriptomic mechanisms of resistance predominate in the presence of active cytotoxic chemotherapy combined with anti-EGFR therapy in the first-line setting, with a greater predominance of acquired MAPK mutations after single-agent anti-EGFR therapy in the later-line setting. The proposed model has implications for prospective studies evaluating anti-EGFR rechallenge strategies guided by acquired MAPK mutations and highlights the need to address transcriptional mechanisms of resistance.